2016
DOI: 10.1097/wnr.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 degradation mediated by calcineurin involved in the neurotoxicity of isoflurane

Abstract: Isoflurane, a commonly used volatile anesthetic, causes widespread neuronal apoptosis in the developing brain of rodents. Signal transducer and activator of transcription-3 (STAT3) signaling is crucial for cell survival during the neural network establishment period. The aim of this study was to determine whether isoflurane would target STAT3 to deliver its neurotoxicity. Mice at postnatal day 7 and primary cortical neurons cultured for 5 days were treated with isoflurane. Our data showed that isoflurane expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The alterations of functional gene abundances in the microbial taxa were predicted based on our 16S rRNA gene datasets by means of PICRUSt (phylogenetic investigation of communities by reconstruction of unobserved state) [25]. As shown in Fig 5, overall, there was no coherent change in the KEGG pathway that was significant ([log10] LDA scores > 2) and consistent with the change of the obese phenotype upon puerarin and/or HFD treatment.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The alterations of functional gene abundances in the microbial taxa were predicted based on our 16S rRNA gene datasets by means of PICRUSt (phylogenetic investigation of communities by reconstruction of unobserved state) [25]. As shown in Fig 5, overall, there was no coherent change in the KEGG pathway that was significant ([log10] LDA scores > 2) and consistent with the change of the obese phenotype upon puerarin and/or HFD treatment.…”
Section: Resultsmentioning
confidence: 89%
“…The animals were anaesthetized by isoflurane using an anesthetizing chamber (MSS International Limited, West Yorkshire, UK) to a sealed plastic box, and the concentration of isoflurane was monitored continuously using a Vamos gas analyzer (Drager, Lübeck, SchleswigHolstein, Germany) [25]. We used 4% concentration of isoflurane for inducing anesthesia and 2% concentration of isoflurane for maintenance, the flow rate was kept at 0.6–0.8 L/min [26, 27].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, NFATc4 mediated light-induced retinal ganglion cell apoptosis by upregulating Fas ligand (FasL) expression on retinal neurons [236], and the overactivation of calcineurin/NFATc3 signaling induced the typical neuronal toxicity and functional alterations observed in murine developing hippocampal neurons following the inhalation of anesthetic isoflurane, including cognitive impairment [237]. A recent study in this model of postoperative cognitive dysfunction revealed that abnormal calcineurin/NFAT signaling associated with isoflurane exposure may mediate its detrimental effects by promoting the degradation of the survival molecule signal transducer and activator of transcription 3 (STAT3) [238]. Moreover, calcineurin/NFATc3 signaling in activated astrocytes played a key role in the induction of alterations in synaptic remodeling and homeostasis observed in the hippocampus in controlled cortical impact injury in rats [39, 128, 239].…”
Section: Controversial Roles In Nervous System Diseasesmentioning
confidence: 99%
“…The primary cortical neurons were cultured in vitro for 5 days (C5) or 14 days (C14) and treated with 1.5% iso urane in a gas mixture of 21% O 2 , 5% CO 2 , and balanced nitrogen for 6 hr as we described previously [9]. In the interaction experiments, neurons were pretreated with FK506 (1mM) 30 min before iso urane exposure.…”
Section: Primary Neuron Culture and Treatmentmentioning
confidence: 99%